ANALISIS PENJUALAN CABLE SUPREME PADA PT. SUMBER MAKMUR ADIPRAYOGA - Yohannes P Kumagaya; Veronika Debora (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
This research aims to know the effect of price and product quality towards sales volume ofcable supreme in PT. Sumber Makmur Adiprayoga. The population that used in this study is 250customers of PT. Sumber Makmur Adiprayoga, and a sample is 100 respondents. Data collectiontechniques in this study was done by conducting interviews, observations, and distributingquestionnaires. Data analysis technique in this study used multiple linier regression, coefficients ofdetermination (R2), T-test, and F-test by using SPSS (Statistical Program and Service Solution) version20.0.Based on the results, the partial test (T-test) obtained t-count of price towards sales volume is6,334 greater than t-table of 1,984 and t-count of quality product towards sales volume is 8,907 greaterthan t-table of 1,984. Based on simultaneous testing (F-test) is f-count of 106,155 greater than f-table of3,09 then it can be concluded price and product quality has significant effect towards volume of cablesupreme in PT. Sumber Makmur Adiprayoga. Result of the coefficients determination (R2) is 0,686indicated that sales volume are influenced by the price and product quality of 68,6% , while the rest of31,4% are influenced by other factors.Based on the conclusions, the suggestion in this research is PT. Sumber Makmur Adiprayogamust provide discounts customers, examine the quality of Cable Supreme products, by improving theaesthetics and reliability of the product, and review the price and quality of products to achieve salesvolume target.